Influence of corn forage type and flaxseed on the productive parameters, meat quality and sensory analysis in Pelibuey lambs - Ramírez, Diana Tamara; Rodriguez, José Reyes Galaviz; Aguilar, Xochitl Gabriela Montalvo; Peñalosa, Patricia Villalobos; Roldán, Pablo Cortés; Calva, Luz Marina Hernández (Emirates Journal of Food and Agriculture, 2020)
The effect of corn straw (CS) or silage (CL), combined with flaxseed (Fx) on meat quality production and sensory analysis of Pelibuey lambs were evaluated. Sixty-four Pelibuey lambs were divided to each of the following treatments: T1) Corn Straw (CS: 16.3%) without flaxseed (Fx) in the diet, T2) CS plus 6% of Fx, T3) Corn silage (CL: 15%) without Fx and T4) CL plus 6% of Fx. Dry matter intake improved by 9.2% with CL vs. CS. The feed conversion improved with the use of CL in 1-14d (P≤ 0.02) and 14-28d (0.05) in 11.7% and 10.4%, respectively. Coordinate b was increased by 38% (P=0.01) in the animals fed with CS. Thus results show that Fx did not influence the physical-chemical and sensory variables of the meat. CL favorably changed the feed intake, flavor and juiciness of the meat, as in the fattening of lambs.